WORK STUDY TECHNIQUES EVALUATION AT BACK-END SEMICONDUCTOR MANUFACTURING - Abd. Rahman, Md. Nizam; Abdullah, Rohana (2012)
Abstract – With the ever increasing labor cost and high labor turnover, performing labor productivity study is imperative for the back-end semiconductor manufacturer to stay competitive. However, an effective technique to perform the work study on the operators is required before any productivity improvement initiatives can be performed. This paper discusses the various techniques being evaluated based on the preset criteria established by the company’s management. Results from the method evaluation will be used to determine the suitable work study technique to be used to perform labor productivity study.